138k views
3 votes
Rewrite the following radical expressions as equivalent exponential expressions.
b. 2(4√3)

1 Answer

3 votes

Answer:


2^(3) .3^{(1)/(2) }.

Explanation:

Here in this problem, we have to rewrite a radical expression as an equivalent exponential expression.

The radical expression is 2(4√3)

Now, 2 ( 4√3)

=( 2 × 4) √3 {Since all the terms are in product form so, we can rearrange it}

= ( 2× 2²) × √3

=2³√3 {Since we know the formula from the property of exponent, xᵃ . xᵇ = x⁽ᵃ⁺ᵇ⁾ }

=
2^(3) .3^{(1)/(2) }.

Therefore,
2^(3) .3^{(1)/(2) } is the required equivalent exponential form. (Answer)

User TerminalWitchcraft
by
5.3k points